Relationship between spontaneous frequency of aneuploidy and cancer risk in 2145 healthy Hungarian subjects - Farkas, Gyöngyi; Jurányi, Zsolt; Székely, Gábor; Kocsis, Zsuzsa S.; Gundy, Sarolta (Mutagenesis, 2016)
Numerical and structural chromosomal abnormalities are the hallmarks of cancer. Whereas the structural chromosome aberrations got more substantial attention for cancer risk assessment in a healthy population, the role of aneuploidy is much less understood in this respect. We analysed the frequency of numerical (and structural) aberrations in peripheral blood lymphocytes of 2145 healthy individuals between 1989 and 2010, taking into account different biological- and exposure-conditions. We also studied to what extent chromosome gains or losses may predict the probability of cancer. The average frequency of all aneuploid cells was 1.78±0.06% in the entire study population, which increased linearly with age. Gender and smoking did not influence the values, however, occupational exposures did. The highest frequency of aneuploidy was found in chemical industry-workers (1.89±0.05%) compared with the lowest value of medical radiation workers (1.44±0.10%), respectively. No correlation was found between numerical and structural chromosomal aberrations. Cancer incidence followed for 1-23 years after the chromosome analysis showed a 1.26-fold relative risk (confidence interval: 1.02-1.58; P = 0.04) for those with higher frequency of aneuploid cells (1.82% vs. 1.44% in controls). Hypodiploidy had higher impact on the cancer risk than hyperdiploidy (1.72% vs. 0.10%). Our findings on the frequency of numerical aberrations in a healthy cohort represent the largest cytogenetic database from one laboratory with an unchanged mechanistic scoring method during a 30-year period, and provide basic information not only for genotoxicological studies but also confirm the association between numerical aberrations and cancer risk.